Diagnostics of the 3 Kv DC Traction Power Network - Jerzy, Wojciechowski; JÃ³zef, Syc; Tomasz, PerzyÅ„ski; Zbigniew, Åukasik (International Journal of Engineering and Technology, 2018)
The railway traction network line is one of the technical elements ensuring proper operation of railway traffic. Due to its technical function and specificity, it is an essential element of the railway infrastructure. That is, why diagnostics of traction networks is a very important issue. In the article, the authors presented issues related to the diagnostics of 3kVDC traction networks. An analysis of traction network faults for a group of power supply areas was also presented. Additionally, calculations of damage indicators in a selected, representative power supply area are presented.Â On the basis of made an analysis authors proposed solutions aimed at minimizing breakdowns in traction networks.Â Â